(untitled) (Research, Society and Development, 2021)
Introduction: The increase in life expectancy as well as behavioral changes have changed the epidemiological profile of HIV/AIDS in Brazil. Objective: to identify the epidemiology of elderly people with HIV/AIDS in Brazil from 2008 to 2018. Methodology: This is an epidemiological study carried out through consultation with DATASUS. Data for the period 2008 to 2018 were consulted. Results: In this period, 21701 new cases of HIV/AIDS were identified in patients aged ≥60, representing 4.87% of the total. elderly, it was verified the relationship between the level of education and the rate of infection, the growth in the number of cases in certain regions and the process of heterosexualization of the disease was noted. Conclusion: HIV/AIDS is today a reality of great challenges for managers and health professionals. We emphasize the possibility of developing and implementing public prevention policies specific to this population, as well as the development of good professional practice capable of meeting the increased demand of elderly people who face this disease.